Future Trends in Work Remote, Videoconferencing and EaD: Exploring Technological Innovations for Collaboration Virtual - Rossini Martins Cardoso, Débora (INFOCOMP Journal of Computer Science, 2025)
With the increase in remote work and distance education (EaD) and the growing use of video conferencing tools and virtual environments for learning and collaborative work, it is essential to ex- plore existing tools to such tasks - as well as pointing out future trends in this constantly evolving field, whether in teaching activities, academic or market work. We can mention the tools for virtual meetings, web-binars and event transmission, enabling the carrying out of teaching activities, presentations and various works, carried out remotely. or hybrid - breaking geographical barriers, allowing everyone to participate regardless of where they are at the moment. The role of augmented reality (AR) in virtual and hybrid meetings and events also stands out - showing the potential for this technology to transform the user experience by providing more immersive and efficient interactions. There is also the integration of collaboration tools in virtual reality (VR) environments, offering spaces for teaching, working and participating in fully immersive virtual events . This article seeks to provide a comprehensive overview of these technological innovations that shape the future of activities carried out remotely - offering valu- able insights for students, teachers, professionals in general, business leaders and researchers interested in maximizing the potential of such digital resources. Furthermore, it is intended to reflect on the im- plications of these trends, by highlighting the potential benefits (in terms of efficiency, productivity and flexibility), while at the same time recognizing the challenges associated with the adoption of these tech- nologies, such as privacy issues.